Pengaruh Teknik Penjualan Affiliate Marketing terhadap Daya Jual Produk di Tokopedia - Dyah Ayu Safitri; Mochammad Isa Anshori (Jurnal Manuhara : Pusat Penelitian Ilmu Manajemen dan Bisnis, 2025)
The study aims to analyze the influence of affiliate marketing sales techniques on product selling power at Toko Pedia. In today's digital era, this technique is increasingly relevant, especially with the increasing number of internet users who prefer to shop online. This study focuses on analyzing the effectiveness of affiliate marketing techniques in increasing product sales in encouraging increased product sales volume and identifying the determining factors that influence it. This study utilizes a qualitative survey method with data collection through questionnaires distributed to affiliates.The method applied is a qualitative survey with data collection through questionnaires addressed to affiliates and consumers at Toko Pedia. The findings of this study are expected to provide important insights for business practitioners in designing more effective marketing strategies and increasing competitiveness in the digital marketplace.